Wind energy and local community perceptions - Lima, Fátima (2013)
Portugal has seen in recent years an increased growth of wind farm’s deployment in its northern region, in accordance with national legal framework and current energy policies. The majority of existing academic studies focusing on impacts (benefits or costs) resulting from deployment of this technology, mainly addressee these aspects from a global point of view. Notwithstanding wind power projects have also been associated with significant impacts directly affecting local communities where these projects were implemented. This paper aims to identify such local impacts, reflecting local community’s perspective through the use of interviews. A comparative analysis of the reported impacts and the way they are being perceived by the local stakeholders, with the results from previous studies on the topic was attempted. Results demonstrated that the majority of interviewees did not point out disadvantages significantly altering their quality of life, revealing a consensual acceptance of benefits from these projects. The major importance of this sort of energy investments and of associated benefits was recognized. Revenues attributed to Communal Land Commission, in charge of managing the land destined to wind farm deployment, were perceived as highly favourable, allowing to answer local community’s needs.